2003
DOI: 10.3758/bf03194586
|View full text |Cite
|
Sign up to set email alerts
|

Auditory imagery from musical notation in expert musicians

Abstract: Anecdotal evidence has suggested that musical notation can trigger auditory images. Expert musicians silently read scores containing well-known themes embedded into the notation of an embellished phrase and judged if a tune heard aloud thereafter was the original theme (i.e., melodic target) or not (i.e., melodic lure). Three experiments were conducted employing four score-reading conditions: normal nondistracted reading, concurrent rhythmic distraction, phonatory interference, and obstruction by auditory stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
117
1
9

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(135 citation statements)
references
References 35 publications
8
117
1
9
Order By: Relevance
“…This result, similar to the findings of Brodsky et al (1998Brodsky et al ( , 1999Brodsky et al ( , 2003, suggests that our previous results did not occur because of qualitative differences between targets and lures. Moreover, the results show no significant differences between the stimulus types for overall PC.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This result, similar to the findings of Brodsky et al (1998Brodsky et al ( , 1999Brodsky et al ( , 2003, suggests that our previous results did not occur because of qualitative differences between targets and lures. Moreover, the results show no significant differences between the stimulus types for overall PC.…”
Section: Discussionsupporting
confidence: 82%
“…The criteria for referral were demonstrable high-level abilities in general music skills relating to performance, literature, theory, and analysis, as well as specific music skills relating to dictation and sight singing. Out of the 74 musicians tested, 26 (35%) passed a prerequisite threshold inclusion criterion demonstrating notational audiation ability; the criterion adopted for inclusion in the study (from Brodsky et al, 1998Brodsky et al, , 1999Brodsky et al, , 2003 represents a significant task performance ( p Ͻ .05 using a sign test) during nondistracted sight reading, reflecting a 75% success rate in a block of 12 items. Hence, this subset (N ϭ 26) represents the full sample participating in Experiment 1.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, improved auditory imagery ability has been observed in musically trained subjects (Aleman, Nieuwenstein, Bocker, & de Haan, 2000). Musical imagery can even be triggered by music notation symbols whose decoding is dependent on musical training (Brodsky, Henik, Rubinstein, & Zorman, 2003).…”
Section: The Knowledge Basementioning
confidence: 99%
“…In fact, during the SCT, humans show smaller temporal variability and better accuracy with auditory rather than visual interval markers [54][55][56]. It has been suggested that the human perceptual system abstracts the rhythmic-temporal structure of visual stimuli into an auditory representation that is automatic and obligatory [118,119]. Thus, it is quite possible that the human auditory system has a privileged access to the temporal and sequential mechanisms working inside the mCBGT circuit in order to determine the exquisite rhythmic abilities of the Homo sapiens [7,21].…”
Section: Neurophysiology Of Rhythmic Behaviour In Monkeysmentioning
confidence: 99%